Cardio- and Cerebrovascular Outcomes of Postoperative Acute Kidney Injury in Noncardiac Surgical Patients With Hypertension - Guangyu, Yan; Jingfeng, Lou; Xing, Liu; Hong, Yuan; Yao, Lu (Frontiers in Pharmacology, 2021)
Background: The cardiovascular and cerebrovascular risk of postoperative acute kidney injury (AKI) in surgical patients is poorly described, especially in the hypertensive population. Methods: We conducted an observational prospective study among all hypertensive patients who underwent elective non-cardiac surgery from January 1st 2012 to August 1st 2017 at The Third Xiangya Hospital. The primary outcome were fatal stroke and fatal myocardial infarction (MI). The secondary outcomes were all-cause mortality. Result: The postoperative cumulative mortality within 3 months, 6 months, 1 year, 2 years, and 5 years were 1.27%, 1.48%, 2.15%, 2.15%, and 5.36%, for fatal stroke, and 2.05%, 2.27%, 2.70%, 3.37%, and 5.61% for fatal MI, respectively, in patients with postoperative AKI. Compared with non-AKI patients, those with postoperative AKI had a significantly higher risk of fatal stroke and fatal MI within 3 months [hazard ratio (HR): 5.49 (95%CI: 1.88-16.00) and 11.82 (95%CI: 4.56-30.62), respectively], 6 months [HR: 3.58 (95%CI: 1.43-8.97) and 9.23 (95%CI: 3.89-21.90)], 1 year [HR: 3.64 (95%CI: 1.63-8.10) and 5.14 (95%CI: 2.50-10.57)], 2 years [HR: 2.21 (95%CI: 1.03-4.72) and 3.06 (95%CI: 1.66-5.64)], and 5 years [HR: 2.27 (95%CI: 1.30-3.98) and 1.98 (95%CI: 1.16-3.20)]. In subgroup analysis of perioperative blood pressure (BP) lowering administration, postoperative AKI was significantly associated with 1-year and 5-year risk of fatal stroke [HR: 9.46 (95%CI: 2.85-31.40) and 3.88 (95%CI: 1.67-9.01), respectively] in patients with ACEI/ARB, and MI [HR: 6.62 (95%CI: 2.23-19.62) and 2.44 (95%CI: 1.22-4.90), respectively] in in patients with CCB. Conclusions: Hypertensive patients with postoperative AKI have a significantly higher risk of fatal stroke and fatal MI, as well as all-cause mortality, within 5 years after elective non-cardiac surgery. In patients with perioperative administration of ACEI/ARB and CCB, postoperative AKI was significantly associated with higher risk of fatal stroke and MI respectively.